Enhanced photoelectric and thermoelectric coupling factor in BiMn2O5 ferroelectric film - Aohan Xu; Chong Guo; Weiqi Qian; Chris R. Bowen; Ya Yang (Advanced Powder Materials)
Ferroelectric film materials have attracted significant interest due to their potential for harvesting various forms of clean energy from natural environmental sources. However, the photoelectric performance of these materials is frequently constrained by heat generation during light absorption, resulting in significant thermal losses. Most of ferroelectric films produce photocurrent and thermocurrent with opposite polarity, thus weakening the coupled photo-thermoelectric output of the devices. Here we report on a LaNiO3/BiMn2O5(BMO)/ITO ferroelectric film to produce photocurrent and thermocurrent with the same polarity. The polarity of the photocurrent generated by the BMO film is shown to be determined solely by the direction of spontaneous polarization, overcoming the detrimental effect of Schottky barrier for energy harvesting in device. We propose a new strategy to enhance the coupling factor, thereby offering valuable new insights for optimizing the utilization of ferroelectric materials in both light and heat energy applications.